Peran Pola Asuh dan Keterlibatan Orang Tua dalam Perkembangan Numerasi Siswa Sekolah Dasar : Analisis dalam Perspektif Paradigma Sosiologi Antropologi - Hignasari, L.Virginayoga; Yamin, Muhamad; Sriartha, I Putu; Mudana, Wayan; Pageh, Made (Adi Widya: Jurnal Pendidikan Dasar, 2025)
Numeracy skills during elementary school are an important foundation for cognitive development and academic success at later levels. This study aims to analyze the role of parenting styles and parental involvement in children's numeracy development through the perspective of the socio-anthropological paradigm. The method used is a qualitative approach with a systematic literature review. The results of the study indicate that the home numeracy environment plays a significant role in children's numeracy development. Supportive parental support and the provision of autonomy increase children's numerical self-confidence and mathematics achievement, while a controlling parenting style has a negative impact. Parents' knowledge of the stages of numeracy development and their ability to manage mathematics anxiety have been shown to influence the quality of support provided. Furthermore, informal numeracy practices within family routines, such as counting while shopping or cooking, are more effective than formal, mechanistic approaches. This study confirms that children's numeracy development is not only a pedagogical domain of school but also a socio-cultural construct that develops through family interactions, values, and daily habits. The implication is that numeracy strengthening needs to be designed in a family-based, collaborative, and contextual manner with local culture in mind.